INNV-12. A SINGLE-INSTITUTION RETROSPECTIVE REVIEW OF PATIENTS WITH CNS TUMORS WHO INITIATED A KETOGENIC DIET. (9th November 2020) - Amaral, Lauren; Welborn, Amelia; Lockshon, Laura; Gresham, Gillian; Panhans, Cristina; Rudnick, Jeremy; Irwin, Scott; Freedland, Stephen; Hu, Jethro
Abstract: BACKGROUND: Many patients with CNS tumors express interest in initiating a ketogenic diet (KD). Following a discussion with the physician regarding the limited clinical evidence of KD for CNS tumors, interested patients were referred for evaluation by an oncology-certified dietitian. METHODS: We performed a single institution retrospective chart review of patients with CNS tumors on a KD. Demographics, clinical characteristics, and diet information were extracted from patient charts. Descriptive statistics were conducted to summarize patterns of adherence to KD across patient characteristics. RESULTS: From May 2016 to May 2018, 40 patients expressed interest in KD; 24 initiated it. M:F = 18:6, median age 46 (range 27–62). Diagnoses: 18 glioblastoma, 1 anaplastic astrocytoma, 2 grade 2 astrocytoma, 1 grade 2 oligodendroglioma, 1 spinal grade 2 astrocytoma, 1 chordoma. 18 tumors with methylated MGMT, 8 with mutant IDH1. At diet initiation, median KPS 80 (range 70–100); median BMI 25.6 (20.8–39). Median days on diet = 190 days; interquartile range 126–673 days; range 24–1479 days. Diet composition: 15 patients on 3:1 diet (grams fat: grams protein + carbs), 7 patients on 2:1, 2 patients on 1:1. 14 patients monitored blood ketone levels. 11 patients stopped KD: 5 for restrictiveness of diet (median 158 days, range 60–239); 1 for decreased KPS (673 days); 1 for excessive weight loss (108 days); 2 for disease progression (24 and 217 days); 2 lost to follow-up (109 and 125 days). In this small sample, no statistically significant associations between time on diet and age / gender / BMI / KPS / diet composition. However, trend toward longer adherence to diet in females, age < 50, 2:1 diet. CONCLUSION: It is feasible for patients with CNS tumors to adopt KD. Results from prospective studies are needed to assess effects on QOL, neurocognition, performance status, and survival.